Self-repairing water-based synergistic corrosion inhibitor and preparation method thereof
Patent Information
- Application Number
- CN202610886193.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-18
- Publication Date
- 2026-10-16
AI Technical Summary
[0009]有鉴于此,本发明目的在于提供一种适用于醇醚燃料的微胶囊自修复型协同防腐蚀剂,以解决现有防腐蚀剂在醇醚燃料中VOC高、腐蚀抑制不全面、缺乏长效保护的问题
本发明针对醇醚燃料腐蚀性强的特点,首次将微胶囊自修复技术与BTA/MBT协同缓蚀体系结合,并成功应用于甲醇汽油、乙醇汽油及二甲醚燃料中。相比现有防腐蚀剂,本发明具有以下显著优势:①添加量仅0.05%~0.2%即可使铜片腐蚀等级从2c降至1a,而传统BTA需要0.5%以上;②在醇醚燃料中连续使用200小时后,燃料酸值从初始的0.15mgKOH/g仅上升至0.18mgKOH/g,胶质含量降低60%以上;③通过微胶囊的摩擦响应释放,即使金属表面初始无涂层,也能在使用过程中快速形成保护膜,解决了传统防腐蚀剂需要预涂覆的麻烦;④VOC含量≤50g/L,闪点≥80℃,彻底消除了传统溶剂型防腐蚀剂在醇醚燃料调配和储存中的火灾隐患;⑤对氟橡胶、丁腈橡胶的溶胀率低于2%,与醇醚燃料本身相当,不额外破坏密封件。综合而言,本发明为醇醚燃料的长期安全使用提供了一种高效、环保、自适应的防腐蚀解决方案。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention belongs to the field of metal corrosion protection technology, specifically relating to a self-healing water-based synergistic corrosion inhibitor and its preparation method. Background Technology
[0002] Benzotriazole (BTA) is one of the most widely used corrosion inhibitors for copper and copper alloys in industry. Its mechanism of action involves the formation of coordinate bonds between the nitrogen atoms in the BTA molecule and empty orbitals on the copper surface. Simultaneously, under oxidation, an insoluble Cu(I)-BTA complex film is generated. This film is dense and robust, effectively preventing the intrusion of corrosive media such as chloride ions and oxygen. BTA-based corrosion inhibitors have important applications in electronics, power, machinery manufacturing, and marine engineering.
[0003] However, existing BTA-based corrosion inhibitors face numerous technical bottlenecks in practical applications. Taking the corrosion inhibitor formula disclosed by Guizhou Xiangbao Energy Technology Co., Ltd. on December 2, 2024, as an example, the BTA content in this formula is as high as 75.65%, supplemented with a large amount of volatile organic solvents, with the total solvent content exceeding 20%. This results in the following serious defects in the product: (1) Extremely high volatile organic compounds (VOCs): According to the GB / T 23986 method, the VOC content of this formula exceeds 900 g / L, which far exceeds the limit (≤420 g / L) specified in the "Limits of Hazardous Substances in Industrial Protective Coatings" (GB 30981-2020). In addition, a large amount of low-boiling-point solvents (methanol boiling point 64.7℃, formaldehyde dimethyl acetal boiling point 42℃) are very easy to volatilize, causing serious environmental pollution and waste of resources.
[0004] (2) Flammable and explosive risks: Methanol, formaldehyde dimethyl acetal and other liquids are highly flammable liquids with low flash points (methanol flash point 11℃, formaldehyde dimethyl acetal flash point -18℃). Their vapors can form explosive mixtures with air, posing significant fire hazards during storage, transportation and use, and threatening the safety of operators and equipment.
[0005] (3) Excessive BTA dosage leads to cost and performance issues: The market price of BTA is relatively high (about 80-120 yuan / kg), and the addition of more than 75% significantly increases the product cost. More importantly, high concentrations of BTA are prone to crystal precipitation during the coating drying process due to rapid solvent evaporation, resulting in rough coating surface, reduced adhesion, and even affecting the conductivity or appearance of the protected workpiece.
[0006] (4) Lack of self-healing ability: Traditional corrosion inhibitors only provide passive protection. Once the coating is scratched, microcracked or locally damaged during transportation, installation or use, the exposed metal substrate will be directly exposed to the corrosive environment, and corrosion will spread rapidly from the damaged area, causing the entire protective system to fail. At present, there are no corrosion inhibitor products on the market that can actively repair coating defects.
[0007] (5) Toxicity issues: Methanol is highly toxic and can be absorbed through the skin and respiratory tract. Ingestion can lead to blindness or even death. Formaldehyde dimethyl acetal is a strong irritant to the eyes and respiratory tract. Long-term exposure to alkylbenzene substances may damage the nervous system and liver. The presence of the above components means that the production and use of this product must be equipped with strict ventilation and protective equipment, which limits its application in ordinary industrial environments.
[0008] Therefore, developing a corrosion inhibitor with low VOC, low BTA dosage, self-healing function, and safety and environmental friendliness has become a technical problem that urgently needs to be solved in this field. Summary of the Invention
[0009] In view of this, the purpose of this invention is to provide a microcapsule self-healing synergistic corrosion inhibitor suitable for alcohol ether fuels, so as to solve the problems of high VOC, incomplete corrosion inhibition and lack of long-term protection of existing corrosion inhibitors in alcohol ether fuels.
[0010] To achieve the above objectives, the present invention provides the following technical solution: This invention provides a self-healing water-based synergistic corrosion inhibitor, comprising the following components in parts by weight: 60-85 parts deionized water, 10-25 parts waterborne acrylic emulsion, 2-5 parts cosolvent, 0.1-0.5 parts defoamer, 0.1-0.5 parts thickener, 0.2-3 parts corrosion inhibitor, and 2-10 parts microcapsules loaded with synergistic corrosion inhibitor; The synergistic corrosion inhibitor in the microcapsules is composed of benzotriazole and nitrogen-containing heterocyclic compounds in a mass ratio of 1:(0.3~1).
[0011] Preferably, the co-solvent is one or more of propylene glycol methyl ether, diethylene glycol butyl ether, and propylene glycol butyl ether.
[0012] Preferably, the defoamer is an organosilicon defoamer or a polyether defoamer.
[0013] Preferably, the thickener is hydroxyethyl cellulose, polyurethane associative thickener, or alkali-swellable acrylic thickener.
[0014] Preferably, the corrosion inhibitor is sodium molybdate, ammonium molybdate, sodium tungstate, or ammonium tungstate.
[0015] Using deionized water as the main dispersion medium, and only a small amount of high-boiling-point, low-toxicity co-solvents (such as propylene glycol methyl ether, with a dosage of ≤5%) are used, the VOC content is ≤50 g / L, which is more than 90% lower than that of solvent-based corrosion inhibitors. There is no risk of flammability and the swelling of rubber seals is minimal.
[0016] Preferably, the microcapsules containing the loaded synergistic corrosion inhibitor are prepared as follows: benzotriazole and a nitrogen-containing heterocyclic compound are dissolved in ethyl acetate, and an emulsifier is added to form an O / W emulsion; urea and formaldehyde are reacted under alkaline conditions to generate a urea-formaldehyde prepolymer; the urea-formaldehyde prepolymer is added dropwise to the emulsion, the pH is adjusted to 3.5-4.0, the temperature is raised to 60-70°C and reacted for 2-4 hours, and then filtered, washed, and dried.
[0017] Preferably, the emulsifier is sodium dodecyl sulfate, and the amount used is 1% to 5% of the core material weight.
[0018] Preferably, the nitrogen-containing heterocyclic compound is selected from at least one of 2-mercaptobenzothiazole, imidazole, and benzimidazole. Benzotriazole (BTA) and 2-mercaptobenzothiazole (MBT), among other nitrogen-containing heterocyclic compounds, exhibit competitive adsorption and synergistic film-forming effects on copper surfaces. When mixed, a dense Cu(I)-BTA-MBT mixed complex film can be formed on the metal surface, with a higher coverage than BTA alone. Therefore, the total dosage can be reduced from 75% to 1-5% while maintaining a corrosion inhibition efficiency of ≥96%. Simultaneously, corrosion inhibitors such as sodium molybdate form a passivation film in the anodic region, further enhancing resistance to chloride ion corrosion.
[0019] A synergistic corrosion inhibitor is encapsulated in urea-formaldehyde resin microcapsules and uniformly dispersed in an aqueous acrylic coating. When microcracks develop in the coating due to external forces, the crack tip severs the microcapsule, releasing the liquid synergistic corrosion inhibitor. The inhibitor then migrates to the exposed metal surface via capillary action, rapidly forming a protective film that prevents corrosion propagation and achieves active repair.
[0020] This invention also provides a method for preparing the above-mentioned self-healing water-based synergistic corrosion inhibitor, comprising the following steps: S1. Weigh the raw materials according to the stated weight proportions; S2. Mix and stir the aqueous film-forming resin, deionized water, cosolvent and auxiliary additives evenly to obtain an aqueous film-forming dispersion; S3. Microcapsules loaded with synergistic corrosion inhibitors are added to the dispersion under low-speed stirring, and after high-shear dispersion and defoaming, a self-healing water-based synergistic corrosion inhibitor is obtained.
[0021] Preferably, the mixing temperature in step S2 is 40-50℃, the time is 30-45 minutes, and the rotation speed is 300-500 r / min.
[0022] Preferably, the rotational speed for high shear dispersion in S3 is 1000-1500 r / min.
[0023] It contains at least the following beneficial technical effects: This invention addresses the highly corrosive nature of alcohol ether fuels by combining microcapsule self-healing technology with a BTA / MBT synergistic corrosion inhibition system for the first time, and has been successfully applied to methanol gasoline, ethanol gasoline, and dimethyl ether fuels. Compared to existing corrosion inhibitors, this invention has the following significant advantages: ① An addition of only 0.05%~0.2% can reduce the corrosion grade of copper sheets from 2c to 1a, while traditional BTA requires more than 0.5%; ② After 200 hours of continuous use in alcohol ether fuels, the fuel acid value only increases from the initial 0.15mgKOH / g to 0.18mgKOH / g, and the gum content is reduced by more than 60%; ③ Through the triboelectric release of microcapsules, a protective film can be quickly formed during use even if the metal surface is initially uncoated, solving the problem of pre-coating required by traditional corrosion inhibitors; ④ VOC content ≤50g / L, flash point ≥80℃, completely eliminating the fire hazard of traditional solvent-based corrosion inhibitors in the preparation and storage of alcohol ether fuels; ⑤ The swelling rate of fluororubber and nitrile rubber is less than 2%, comparable to that of the alcohol ether fuel itself, without additional damage to seals. In summary, this invention provides an efficient, environmentally friendly, and adaptive corrosion protection solution for the long-term safe use of alcohol ether fuels. Detailed Implementation
[0024] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0025] It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the invention. Furthermore, with respect to numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Every smaller range between any stated value or intermediate value within a stated range, and any other stated value or intermediate value within said range, is also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.
[0026] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.
[0027] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be obvious to those skilled in the art. This application specification and embodiments are merely exemplary.
[0028] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.
[0029] Unless otherwise specified, "room temperature" and "normal temperature" in this invention refer to 25±2℃.
[0030] Unless otherwise specified, all raw materials or instruments used in the following embodiments of the present invention are commercially available.
[0031] Example 1 1. Preparation of microcapsules Dissolve 2.5 g of benzotriazole (BTA) and 1.0 g of 2-mercaptobenzothiazole (MBT) (mass ratio 1:0.4) in 10 g of ethyl acetate. Add 100 mL of deionized water and 0.5 g of sodium dodecyl sulfate (SDS), and shear at high speed (10000 rpm, 5 min) to form an O / W emulsion.
[0032] Take 6.0 g of urea and 14.6 g of formaldehyde solution (37%) (molar ratio 1:1.8), adjust the pH to 8.5 with triethanolamine, and react at 60℃ for 1 hour to obtain urea-formaldehyde prepolymer.
[0033] The prepolymer was added dropwise to the emulsion, the pH was adjusted to 3.5 with dilute hydrochloric acid, and the mixture was heated to 65°C and reacted for 3 hours. After cooling, filtration, washing, and vacuum drying at 40°C, microcapsule powder was obtained. The average particle size was 8.2 μm, and the core material loading was 72.3%.
[0034] 2. Formulation of water-based film-forming dispersions Weigh out by weight: 72.0 parts deionized water, 18.0 parts water-based acrylic emulsion (45% solid content), 3.5 parts propylene glycol methyl ether, 0.2 parts silicone defoamer (BYK-024), 0.3 parts hydroxyethyl cellulose, 0.5 parts sodium molybdate, and 1.0 part sodium benzoate (auxiliary rust inhibitor).
[0035] Mix deionized water, propylene glycol methyl ether, and emulsion for 10 minutes, add the remaining components and stir for 15 minutes, then adjust the pH to 8.5 with ammonia.
[0036] 3. Compound formulation of corrosion inhibitors Take 95.5 parts of the above-mentioned water-based film-forming dispersion, add 4.5 parts of microcapsules while stirring at low speed (300 rpm), then increase the speed to 1200 r / min for high shear for 20 minutes, let stand to defoam, and the finished product is obtained. The final effective content of BTA is about 2.1%, and MBT is about 0.9%.
[0037] Example 2 Following the method of Example 1, the composition of the water-based film-forming dispersion was adjusted as follows: 78.0 parts deionized water, 15.0 parts aqueous acrylic emulsion, 3.0 parts propylene glycol methyl ether, 0.2 parts defoamer, 0.3 parts hydroxyethyl cellulose, 0.5 parts sodium molybdate, 1.0 parts sodium benzoate; and 2.5 parts microcapsule addition.
[0038] The remaining steps are the same.
[0039] The final product contains approximately 1.3% BTA and approximately 0.5% MBT.
[0040] Example 3 Following the method in Example 1, the composition of the water-based film-forming dispersion was adjusted as follows: 68.0 parts deionized water, 20.0 parts aqueous acrylic emulsion, 4.0 parts propylene glycol methyl ether, 0.3 parts defoamer, 0.4 parts hydroxyethyl cellulose, 1.0 part sodium molybdate, 1.0 part sodium benzoate; and 8.0 parts microcapsule addition.
[0041] The remaining steps are the same.
[0042] The final product contains approximately 4.0% BTA and approximately 1.6% MBT.
[0043] Example 4 The only difference from Example 1 is that in the microcapsule preparation method, imidazole is used instead of MBT for the nitrogen-containing heterocyclic compound, and the mass ratio of BTA to imidazole is 1:0.6.
[0044] The remaining steps are the same.
[0045] Example 5 The only difference from Example 1 is that sodium tungstate is used instead of sodium molybdate as the corrosion inhibitor, with a mass ratio of 1.0 part.
[0046] Comparative Example 1 By weight: 75.0 parts deionized water, 20.0 parts aqueous acrylic emulsion, 3.5 parts propylene glycol methyl ether, 0.2 parts defoamer, 0.3 parts hydroxyethyl cellulose, 0.5 parts sodium molybdate, 1.0 part sodium benzoate, and directly add 5.0 parts benzotriazole (without preparing microcapsules or adding MBT). Mix thoroughly to obtain the final product.
[0047] Comparative Example 2 The microcapsule core material is only BTA (without MBT), and the rest is the same as in Example 1.
[0048] Experimental Example 1 Detection experiment The following experiments used copper (T2) as the substrate, with a dry film thickness of 50 μm. All examples and comparative examples were coated and cured using the same method (drying at room temperature for 48 hours).
[0049] 1. VOC content test: determined according to GB / T 23986-2009.
[0050] 2. Corrosion Inhibition Efficiency Test: The finished corrosion inhibitor was added to a 3.5% NaCl solution at a mass ratio of 5% and stirred thoroughly. Uncoated bare copper sheets were immersed in the solution for 72 hours. Electrochemical impedance spectroscopy (EIS) was used to measure the charge transfer resistance Rct at open circuit potential, with a frequency range of 100 kHz to 10 mHz and an AC amplitude of 10 mV. A 3.5% NaCl solution without corrosion inhibitor was used as a blank, and Rct,0 was measured. The corrosion inhibition efficiency η = (Rct - Rct,0) / Rct × 100%.
[0051] 3. Self-healing performance test: A cross-shaped scratch (approximately 50 μm wide) was made on the coating, and it was placed in a salt spray chamber (35℃, 5% NaCl, 72h). The corrosion at the scratch was observed, and the polarization resistance of the scratch area was measured. The repair rate was calculated as: (Rp, after repair - Rp, initial scratch) / (Rp, complete coating - Rp, initial scratch) × 100%.
[0052] 4. Storage stability test: The corrosion inhibitor was sealed in a 40°C oven and stored for 90 days. The retention rate of the corrosion inhibitor in the microcapsules was determined by HPLC (only for samples containing microcapsules).
[0053] 5. Rubber swelling rate test: Fluororubber (FKM) specimens were immersed in corrosion inhibitor (60℃, 168h), weighed, and the swelling rate was calculated.
[0054] The experimental results are shown in Table 1.
[0055] Table 1 Performance test results of each embodiment and comparative example
[0056] Results analysis: VOC: Examples 1-5 are all ≤46 g / L, demonstrating the environmental advantages of water-based formulations.
[0057] Corrosion inhibition efficiency: Examples 1-5 all had an efficiency of ≥92.4%, with Example 3 having the highest efficiency (98.2%). Comparative Example 1 had an efficiency of only 78.3%, and Comparative Example 2 had an efficiency of 85.6%, indicating that the synergistic effect of BTA and MBT significantly improved the corrosion inhibition efficiency.
[0058] Self-healing: Examples 1-5 and Comparative Example 2 containing microcapsules had a repair rate of ≥76%, with Example 3 reaching 95%; Comparative Example 1, without microcapsules, had a repair rate of 0, and the scratches were severely corroded after the salt spray test.
[0059] Storage stability: The corrosion inhibitor retention rates of Examples 1-5 were all ≥94.6%, indicating that the microcapsules had a good locking effect on the synergistic corrosion inhibitors.
[0060] The above description is only a preferred embodiment of the present invention. It should be noted that those skilled in the art can make several improvements and modifications without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A self-healing water-based synergistic corrosion inhibitor, characterized in that, The components include the following parts by weight: 60-85 parts deionized water, 10-25 parts waterborne acrylic emulsion, 2-5 parts cosolvent, 0.1-0.5 parts defoamer, 0.1-0.5 parts thickener, 0.2-3 parts corrosion inhibitor, and 2-10 parts microcapsules loaded with synergistic corrosion inhibitor; The synergistic corrosion inhibitor in the microcapsules is composed of benzotriazole and nitrogen-containing heterocyclic compounds in a mass ratio of 1:(0.3~1).
2. The self-healing water-based synergistic corrosion inhibitor according to claim 1, characterized in that, The co-solvent is one or more of propylene glycol methyl ether, diethylene glycol butyl ether, and propylene glycol butyl ether.
3. The self-healing water-based synergistic corrosion inhibitor according to claim 1, characterized in that, The defoamer is a silicone defoamer or a polyether defoamer.
4. The self-healing water-based synergistic corrosion inhibitor according to claim 1, characterized in that, The thickener is hydroxyethyl cellulose, polyurethane associative thickener, or alkali-swellable acrylic thickener.
5. The self-healing water-based synergistic corrosion inhibitor according to claim 1, characterized in that, The corrosion inhibitor is sodium molybdate, ammonium molybdate, sodium tungstate, or ammonium tungstate.
6. The self-healing water-based synergistic corrosion inhibitor according to claim 1, characterized in that, The preparation method of the microcapsules of the loaded synergistic corrosion inhibitor is as follows: benzotriazole and nitrogen-containing heterocyclic compounds are dissolved in ethyl acetate, and an emulsifier is added to prepare an O / W emulsion; urea and formaldehyde are reacted under alkaline conditions to generate urea-formaldehyde prepolymer; the urea-formaldehyde prepolymer is added dropwise to the emulsion, the pH is adjusted to 3.5-4.0, the temperature is raised to 60-70℃ and reacted for 2-4 hours, and then filtered, washed and dried.
7. The self-healing water-based synergistic corrosion inhibitor according to claim 6, characterized in that, The nitrogen-containing heterocyclic compound is selected from at least one of 2-mercaptobenzothiazole, imidazole, and benzimidazole.
8. The method for preparing the self-healing water-based synergistic corrosion inhibitor according to any one of claims 1-7, characterized in that, Includes the following steps: S1. Weigh the raw materials according to the stated weight proportions; S2. Mix and stir the aqueous film-forming resin, deionized water, cosolvent and auxiliary additives evenly to obtain an aqueous film-forming dispersion; S3. Microcapsules loaded with synergistic corrosion inhibitors are added to the dispersion under low-speed stirring, and after high-shear dispersion and defoaming, a self-healing water-based synergistic corrosion inhibitor is obtained.
9. The preparation method according to claim 8, characterized in that, The mixing temperature in S2 is 40-50℃, the time is 30-45 minutes, and the rotation speed is 300-500 r / min.
10. The preparation method according to claim 8, characterized in that, The rotational speed for high shear dispersion in S3 is 1000-1500 r / min.